THE SUB-CHRONIC TOXICITY TEST OF MENIRAN (Phyllanthus niruri L.) AND PEGAGAN (Centella asiatica) EXTRACT IN WISTAR STRAIN RATS ON LIVER AND KIDNEY FUNCTION - Endang Darmawan; Iin Narwanti; Siti Fatmawati Fatimah; Ira Aprilia Wulandari; Ria Putri Salma; Dzulhaifa Dzulhaifa (Sanata Dharma University, 2019)
Meniran (Phyllantus niruri L.) and Pegagan (Centella asiatica L.) was proven had activity that considered as an antioxidant. However, the safety was not confirmed. This research is intended to evaluate sub-chronic toxicity of standardized combination extract of meniran and pegagan on liver and kidney function. This research used post-test-control design. Twenty female and twenty male Wistar strain rats divided into 4 groups. The first group was controlled in dosage of CMC Na 0.5%. The others were given a combination of meniran and pegagan extract in ratio with different dosage (50:50; 250:250; and 1250:1250 mg/KgBW). Sub-chronic toxicity test of meniran and pegagan combination was given orally once a day for 28 consecutive days. On the 29th day, all the rats were sacrificed and blood samples were analyzed using automatic analyzer. SGOT, SGPT, BUN, and creatinine value were statistically analyzed using one way ANOVA with post hoc LSD (p0.05). The results show that treatment of meniran and gotu kola combination had no significantly different of SGOT and creatinine value of male and female rats, and SGPT value of male rats (p0.05). The treatment of meniran and gotu kola combination had significantly different of BUN value of male and female rats, and SGPT value of female rats (p0.05) but still within normal range. Based on this study, it can be concluded that orally administered of meniran and gotu kola extract combination at doses 50:50 mg/KgBW; 250:250 mg/KgBW; and 1250:1250 mg/KgBW had no affected on SGOT, SGPT, BUN and creatinine value of Wistar strain rats on sub-chronic administration for 28 consecutive days.